Preoperative Serum Anti-Mullerian Hormone Level in Women with Ovarian Endometrioma and Mature Cystic Teratoma - Kim, Ju Yeong; Jee, Byung Chul; Suh, Chang Suk; Kim, Seok Hyun (Yonsei medical journal, 2013)
To investigate whether preoperative serum anti-mullerian hormone (AMH) levels are lower in women with ovarian endometrioma and in women with mature cystic teratoma of the ovaries. In a tertiary university hospital, a retrospective case-control study was performed. Serum AMH levels between an advanced (stage III and IV) endometrioma group (n=102) and an age- and body mass index (BMI)-matched control group were compared. Serum AMH levels between an ovarian mature cystic teratoma group (n=48) and age- and BMI-matched controls were also compared. Absolute serum AMH and multiples of the median for AMH (AMH-MoM) relevant to Korean standards were lower in the endometrioma group than controls, but this was not statistically significant (mean±SEM, 2.9±0.3 ng/mL vs. 3.3±0.3 ng/mL, p=0.28 and 1.3±0.1 vs. 1.6±0.1, p=0.29, respectively). Specifically, the stage IV endometriosis group (n=51) exhibited significantly lower serum AMH and AMH-MoM (2.1±0.3 vs. 3.1±0.4 ng/mL, p=0.02 and 1.1±0.1 vs. 1.7±0.2, p=0.03, respectively). Serum AMH and AMH-MoM levels were similar between stage III endometriosis and controls (3.7±0.5 vs. 3.4±0.5 ng/mL and 1.6±0.2 vs. 1.5±0.2, respectively), as well as between the mature cystic teratoma group and controls (4.0±0.5 ng/mL vs. 4.0±0.5 ng/mL and 1.6±0.2 vs. 1.6±0.3, respectively). Interestingly, AMH-MoM level was negatively correlated with endometriosis score with statistical significance (r²=0.13, p<0.01). In women with advanced ovarian endometrioma, preoperative serum AMH values tended to be lower than those for age and BMI-matched controls. Notably, stage IV endometrioma appeared to be closely associated with decreased ovarian reserve, even before operation. Clinicians should keep this information in mind before undertaking surgery of ovarian endometrioma.